2014
DOI: 10.1111/dom.12399
|View full text |Cite
|
Sign up to set email alerts
|

Initial combination of linagliptin and metformin compared with linagliptin monotherapy in patients with newly diagnosed type 2 diabetes and marked hyperglycaemia: a randomized, double‐blind, active‐controlled, parallel group, multinational clinical trial

Abstract: Aims:To evaluate glucose-lowering treatment strategies with linagliptin and metformin in people with newly diagnosed type 2 diabetes and marked hyperglycaemia, a prevalent population for which few dedicated studies of oral antidiabetes drugs have been conducted. Methods:A total of 316 patients, with type 2 diabetes diagnosed for ≤12 months and with glycated haemoglobin (HbA1c) concentration in the range 8.5-12.0%, were randomized 1:1 to double-blind, free-combination treatment with linagliptin 5 mg once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…Almost all (140/144) studies reported on drop‐out rates between treatment arms. Of these, one third of studies (42/140 or 30%) were considered high risk of attrition bias, either due to a higher drop‐out rates in the treatment compared to placebo arms or specific mention of participant study withdrawal due to hypoglycaemia . Six studies were found to have a high risk of bias for selective reporting, either for providing only a range of hypoglycaemia outcomes or reporting hypoglycaemia data only for the extension phase or insufficient details on the severity of episodes …”
Section: Resultsmentioning
confidence: 99%
“…Almost all (140/144) studies reported on drop‐out rates between treatment arms. Of these, one third of studies (42/140 or 30%) were considered high risk of attrition bias, either due to a higher drop‐out rates in the treatment compared to placebo arms or specific mention of participant study withdrawal due to hypoglycaemia . Six studies were found to have a high risk of bias for selective reporting, either for providing only a range of hypoglycaemia outcomes or reporting hypoglycaemia data only for the extension phase or insufficient details on the severity of episodes …”
Section: Resultsmentioning
confidence: 99%
“…2,3 Although this study did not evaluate patients with marked hyperglycaemia, a previous study showed that the initial combination of linagliptin plus metformin achieved large reductions in HbA 1c levels in patients with a mean baseline HbA 1c level of 9.8%, without increasing hypoglycaemia or other adverse effects compared with linagliptin monotherapy. 31 The improvements in efficacy from using an intensive combination treatment strategy should not be at the expense of worsening safety and tolerability profiles. In this study, there were no clinically meaningful differences in the frequencies of AEs between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with stepwise therapy, combination therapy offers some potential advantages, including earlier and greater reductions in HbA1c, and may allow greater preservation and restoration of β‐cell function. Clinical trials have demonstrated that, in patients newly diagnosed with T2D, combination treatment using therapies with complementary mechanisms results in faster and greater HbA1c reductions, and more rapid achievement of glycaemic targets, compared with initial monotherapy . A systematic review and meta‐analysis of 15 randomized controlled trials (RCTs) showed that initial therapy with metformin combined with other oral agents (TZDs, insulin secretagogues, DPP‐4 inhibitors, or SGLT2 inhibitors) resulted in significant improvements in HbA1c and increases in attainment of glycaemic goals (HbA1c <7.0%) compared with metformin monotherapy .…”
Section: Combination Therapymentioning
confidence: 99%